Single-Nozzle Flame Synthesis of Spinel ZnSnO Nanoparticles for Selective Detection of Formic Acid - Darinee Kaewsiri (2020)
© 2001-2012 IEEE. In this research, flame spray pyrolysis (FSP) was used to synthesize spinel Zn2SnO4 nanoparticles for the first time based on the precisely designed stoichiometric chemistry of organic precursor solution driven through a single FSP nozzle. The characterization results based on X-ray diffraction, transmission electron microscopy and nitrogen adsorption confirmed the formation of spinel cubic Zn2SnO4 phase with high phase purity and high specific surface area of 78.8 m2/g. The gas-sensing properties of Zn2SnO4 sensors measured in dry air at 200-400 °C revealed high HCOOH selectivity against several other volatile organic acids, volatile organic compounds and environmental gases with a high and repeatable response of 16.5 towards 1000 ppm HCOOH at an optimal operating temperature of 350 °C.